The Relationship between Novice and Experienced Teachers' Self-efficacy for Personal Teaching and External Influences. (13th May 2015) - Shohani, Saeedeh; Azizifar, Akbar; Gowhary, Habib; Jamalinesari, Ali
Abstract: This study investigates the effect of teachers' self-efficacy on personal teaching and external influences. The study involves 18 novice and 18 experienced English teachers teaching at Ilam high schools from March to September of 2014. Data were collected through a questionnaire. Teacher's questionnaire consisted of 36 Likert scale items. To analyze the data, t-tests were applied. When the two groups were compared, novice and experienced teachers were found to differ in their self-efficacy for classroom management, but not in their efficacy for personal teaching and external influences. In order to improve teachers' efficacy for personal teaching and external influences in-service training programs and regular meetings where teachers share their experiences can be held.